2017
DOI: 10.1002/ptr.5932
|View full text |Cite|
|
Sign up to set email alerts
|

Epoxyazadiradione Purified from the Azadirachta indica Seed Induced Mitochondrial Apoptosis and Inhibition of NFκB Nuclear Translocation in Human Cervical Cancer Cells

Abstract: Epoxyazadiradione (EAD) is an important limonoid present in Neem (Azadirachta indica) plant. In the present study, we have purified EAD from Neem seed and studied its anticancer potential in human cervical cancer (HeLa) cells. Cell proliferation inhibition studies indicated that the GI value of EAD is 7.5 ± 0.0092 μM in HeLa cells, whereas up to 50 μM concentrations EAD did not affect the growth of normal H9C2 cells. The control drug cisplatin inhibited the growth of both HeLa and H9C2 cells with a GI value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Increase in activity of caspase IX and release of active cytochrome-c with inhibition of nuclear translocation factor in HeLa cells was noted. The results were comparable to standard drug, cis-platin which suggested epoxyazadiradione as an alternative chemotherapeutic agent (Shilpa et al, 2017). Seed extract showed significant activity against chronic and acute inflammatory diseases.…”
Section: Antipyretic Analgesic Antinociceptic Antiproliferativementioning
confidence: 57%
“…Increase in activity of caspase IX and release of active cytochrome-c with inhibition of nuclear translocation factor in HeLa cells was noted. The results were comparable to standard drug, cis-platin which suggested epoxyazadiradione as an alternative chemotherapeutic agent (Shilpa et al, 2017). Seed extract showed significant activity against chronic and acute inflammatory diseases.…”
Section: Antipyretic Analgesic Antinociceptic Antiproliferativementioning
confidence: 57%
“…It is isolated from the leaves and flowers of a traditional medicinal plant, Azadirachta indica (Neem). Besides nimbolide, other limonoids such as azadirachtin, nimbidin, and epoxyazadiradione have also shown various beneficial therapeutic activities, including anti‐inflammatory, and anticancer 3‐11 . Notably, available reports suggest that among all the limonoids, nimbolide is the most potent anticancer agent 12 …”
Section: Introductionmentioning
confidence: 99%
“…Besides nimbolide, other limonoids such as azadirachtin, nimbidin, and epoxyazadiradione have also shown various beneficial therapeutic activities, including anti-inflammatory, and anticancer. [3][4][5][6][7][8][9][10][11] Notably, available reports suggest that among all the limonoids, nimbolide is the most potent anticancer agent. 12 Numerous in vitro and in vivo studies have demonstrated the promising therapeutic efficacy of nimbolide against breast, colon, prostate, pancreatic, cervical, renal, and oral cancers.…”
mentioning
confidence: 99%
“…Isolation and characterization of EAD were done as described in our previous report. [15] Briefly, EAD was isolated from the neem seed cake using repeated petroleum ether cum acetone extraction, chromatography, and crystallization process to yield 1.895 g/kg of cake. The compound was later characterized by comparing its spectroscopic data (Fourier-transform infrared spectroscopy, 1 H nuclear magnetic resonance [ 1 HNMR], 13 C NMR) and high-performance liquid chromatography profile with the existing literature.…”
Section: Test Compound Preparationmentioning
confidence: 99%
“…Previously, we have reported the purification of EAD from the petroleum ether extract of neem seeds and their anticancer effects/ mechanism in human cervical cancer cells. [15] In the present paper, Fluorometric Assay Kit (BioVision).…”
mentioning
confidence: 99%